Spraying-assisted layer-by-layer assembled flame-retardant cotton fabric and preparation method thereof
By spraying and assisting layer assembly method, silane coupling agent, oxidized single-wall carbon nanoangle and ammonium polyphosphate are alternately sprayed on the surface of cotton fabrics, the problem of flame retardant efficiency in the prior art depends on substrate matching, and high efficiency is achieved. Environmentally friendly flame retardant effect.
Patent Information
- Application Number
- CN202411760804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has the problem that flame retardant efficiency depends on the mutual matching of the APP coating and the fabric substrate in improving the flame retardant properties of cotton fabrics, and the layer-layer assembly method has the disadvantages of long preparation time and easy contamination of the assembly solution.
Using spray-assisted layer assembly method, silane coupling agent, oxidized single-wall carbon nanoangle and ammonium polyphosphate are alternately sprayed on the surface of cotton fabric to construct an expanded flame retardant coating.
It realizes efficient flame retardant effects with simple process and easy regulation, gentle conditions, shortened processing time, green and environmentally friendly, and improves the flame retardant performance of cotton fabrics.
Smart Images

Figure CN119411409A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant textile material preparation, and in particular relates to a spray-assisted layer-by-layer assembled flame-retardant cotton fabric and a preparation method thereof. Background Art
[0002] Cotton fabrics have been widely used in clothing, bedding, interior decoration and other fields due to their good air permeability, moisture absorption, biocompatibility and biodegradability. Moreover, with the improvement of people's living standards and the rapid development of the textile industry, the market demand for cotton textiles has also increased. However, cotton fabrics have the disadvantages of being easily thermally degraded, ignited and burned, which greatly limits the development of cotton fabrics in some special fields.
[0003] In recent years, various methods have been developed to obtain flame-retardant cotton fabrics in order to improve the flame retardancy of cotton fabrics and avoid fire accidents caused by the burning of cotton fabrics. Ammonium polyphosphate (APP)-based coatings have attracted widespread attention due to their non-toxicity, good thermal stability and low price. APP, as the main acid source, can cooperate well with fabrics (carbon source) to establish an intumescent flame retardant system at the expense of consuming the fabric substrate during combustion.
[0004] However, the flame retardant efficiency of APP depends on the mutual matching between the APP coating and the fabric substrate. In the case of improper proportions or different substrates, the flame retardant efficiency may deteriorate. Therefore, in order to improve the flame retardant efficiency, an additional carbon source is needed to construct an intumescent flame retardant coating together with APP. Carbon-based nanomaterials (graphene, carbon nanotubes, etc.) have extraordinary performance in terms of polymer carbonization quality, thermal stability and mechanical properties due to their outstanding carbon-rich structure. However, the application of carbon-based nanomaterials is difficult. Taking carbon nanotubes as an example, they are expensive and have certain toxicity. The preparation process requires the addition of catalysts, which makes the procedure complicated.
[0005] In addition, the layer-by-layer assembly method has been widely used to prepare coatings containing ammonium polyphosphate (APP) due to its convenience, ease of operation and environmental friendliness. Generally speaking, the layer-by-layer assembly method is to alternately immerse the substrate in an aqueous solution of polyelectrolytes with opposite charges through electrostatic interaction, so that the two polyelectrolytes with different charges are orderly and compactly combined together, and a multilayer film structure is obtained by repeating this process many times. This method can effectively control the thickness, hierarchical structure and morphology of the coating on the surface of the substrate. However, this method also has disadvantages such as long preparation time and easy mutual contamination between assembly solutions.
[0006] Therefore, optimizing the formulation of flame-retardant coatings containing ammonium polyphosphate and further improving the layer-by-layer assembly method are technical issues that still need to be solved in the development of flame-retardant fabric technology. Summary of the invention
[0007] In order to solve the above technical problems, one of the objectives of the present invention is to provide a method for preparing a flame-retardant cotton fabric assembled layer by layer with the aid of spraying.
[0008] The present invention adopts the following technical solutions:
[0009] A method for preparing a flame-retardant cotton fabric assembled layer by layer with spraying assistance, comprising the following steps:
[0010] S1. After the cotton fabric is washed and dried, it is soaked in a sodium hydroxide solution of a set concentration. After the soaking is completed, it is washed again until the pH value of the cotton fabric washing wastewater is neutral, and the cotton fabric is dried;
[0011] S2. spraying 1 to 5 wt% silane coupling agent solution, 0.1 to 1 wt% oxidized single-walled carbon nanohorn solution, 1 to 5 wt% silane coupling agent solution and 2 to 5 wt% ammonium polyphosphate solution on the surface of the cotton fabric in sequence, drying the cotton fabric after each spraying, and spraying in a cycle until the desired number of layers is reached;
[0012] S3. Drying the cotton fabric to obtain the desired flame-retardant cotton fabric.
[0013] Preferably, the number of cycles of the cyclic spraying is 1 to 4 times.
[0014] Preferably, the silane coupling agent is 3-aminopropyltriethoxysilane.
[0015] Preferably, the single spraying amount of the silane coupling agent solution, the oxidized single-walled carbon nanohorn solution and the ammonium polyphosphate solution is the same, and the spraying ratio is 1mL:8cm 2 .
[0016] Preferably, the concentration of the sodium hydroxide solution is 0.25 to 0.5 mol / L, and the soaking time is 10 to 20 min.
[0017] Preferably, in steps S1-S3, the drying temperature is 50-80°C.
[0018] The second object of the present invention is to provide a flame-retardant cotton fabric, wherein 1-4 flame-retardant structural layers are deposited on the surface of the flame-retardant cotton fabric, and the flame-retardant structural layers are composed of a silane coupling agent layer, an oxidized single-walled carbon nano-horn layer, a silane coupling agent layer, and an ammonium polyphosphate structural layer, which are compounded in sequence from the outside to the inside, and the thickness of each of the flame-retardant structural layers is 140 μm, wherein the thickness of the silane coupling agent layer, the oxidized single-walled carbon nano-horn layer, the silane coupling agent layer, and the ammonium polyphosphate structural layer are all 40 μm.
[0019] The beneficial effects of the present invention are:
[0020] 1) The present invention effectively combines the spraying method with the layer-by-layer assembly method. By using a simple spraying device, polyelectrolytes with different charges are sprayed on the surface of cotton fabric in an orderly manner, and finally an intumescent flame-retardant coating composed of a silane coupling agent, oxidized single-walled carbon nanohorns, and ammonium polyphosphate is constructed. Compared with the existing coating preparation technology, the present invention has the advantages of simple and easy control process, mild conditions, effective shortening of processing time, and green environmental protection. Orderly alternating spraying can also avoid cross contamination between assembly liquids, which is conducive to large-scale industrial production.
[0021] 2) For the first time, a new type of carbon nanomaterial, oxidized single-walled carbon nanohorns, was used as a member of the flame retardant system. It was oxidized to prepare an anionic polyelectrolyte that was uniformly dispersed and stable in water, and then alternately assembled with silane coupling agent and ammonium polyphosphate on the surface of cotton fabric to prepare an intumescent flame retardant coating with high flame retardant effect. Among them, ammonium polyphosphate can be used as an acid source and a gas source at the same time to promote the dehydration and carbonization of cotton fabric and oxidized single-walled carbon nanohorns; the presence of oxidized single-walled carbon nanohorns can improve the carbonization effect and increase the stability of the carbon layer. The silicon element in the silane coupling agent can produce a synergistic effect with phosphorus and nitrogen elements to jointly improve the flame retardant properties of cotton fabrics.
[0022] 3) The coating provided by the present invention can give cotton fabric a flame retardant mechanism of carbon nano-based ternary self-assembled coating, that is, when the coated cotton fabric is ignited, APP can play a catalytic carbonization effect and produce ammonia and water, wherein the polyphosphoric acid generated by the thermal degradation of APP can promote the dehydration and carbonization of cotton fabric and single-walled carbon nanohorns. The role of oxidizing single-walled carbon nanohorns to enhance flame retardancy is mainly to: ① improve the carbonization effect, increase the stability of the carbon layer, and thus enhance the protective effect of the physical barrier; ② utilize the rich hydroxyl and carboxyl groups on its surface to absorb heat and cool the substrate, slow down the combustion process, and suppress the fire; ③ the unique "Dahlia" structure can absorb part of the combustible gas. In addition, it can be seen from XPS analysis that the APTES hydrolysis product forms a hybrid carbon layer containing Si-OSi / Si-P / Si-N bonds during the thermal degradation of cotton fabrics. This silicon-containing carbon layer can be used as a heat-insulating layer to protect cotton fabrics from further erosion by fire. Finally, due to the expansion of the carbon layer and the generation of volatile gases, a large number of raised bubble-like structures appear on the surface of the cotton fabric, which hinders the transfer of heat and oxygen, thereby giving the cotton fabric good flame retardant properties.
[0023] 4) Compared with carbon materials such as carbon nanotubes or graphene, the oxidized single-walled carbon nanohorn raw material used in the present invention has a simple preparation method, does not require a catalyst in the preparation process, and does not require the use of fluorine-containing compounds and halogen-containing flame retardants. It has high purity and yield, a wide source, is non-toxic and harmless, and is in line with the development direction of safety and environmental protection.
[0024] 5) The flame-retardant cotton fabric provided by the method has excellent flame-retardant properties and has broad application prospects in the fields of protective clothing, home decoration, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 3 are scanning electron microscope images of pure cotton fabric and flame retardant cotton fabric prepared in Example 4, wherein a1 and a2 are pure cotton fabrics, and b1 and b2 are flame retardant cotton fabrics.
[0026] Figure 2 TG / DTG curves of pure cotton fabric and flame-retardant cotton fabric prepared in Example 4 under nitrogen and air atmospheres.
[0027] Figure 3 3 and 4. The vertical combustion test diagram of pure cotton fabric and flame-retardant cotton fabric prepared in Example 4, a0-a2 in the figure represent pure cotton fabric, b0-b2 represent flame-retardant cotton fabric; the left figure in the figure is the result 5s after ignition, the middle figure is the result 2s after removing the ignition source, and the right figure is the carbon residue after combustion.
[0028] Figure 4 It is a heat release rate curve diagram of pure cotton fabric and flame retardant cotton fabric prepared in Example 4.
[0029] Figure 5 This is a scanning electron microscope image of the carbon residue after vertical combustion of pure cotton fabric and the flame-retardant cotton fabric prepared in Example 4.
[0030] Figure 6 It is the Raman spectrum of the carbon residue after vertical combustion of pure cotton fabric and the flame-retardant cotton fabric prepared in Example 4. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in more detail below in conjunction with the embodiments and drawings.
[0032] Unless otherwise specified, the oxidized carbon nanohorns in this embodiment refer to oxidized single-walled carbon nanohorns.
[0033] The oxidized single-walled carbon nanohorns used in this application can be purchased or obtained using existing preparation methods using single-walled carbon nanohorns. The reference preparation method is, for example: single-walled carbon nanohorns (SWCNHs) are pre-treated with nitric acid oxidation, SWCNHs are placed in a flat-bottomed flask, 7M nitric acid is added, and reflux oxidation is carried out at 110°C for 30 minutes. The oxidized product is then washed with a large amount of deionized water and filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm until the pH value of the filtrate is close to 7; the obtained oxidized carbon nanohorns (SWCNHs-o) are placed in a 60°C oven overnight to dry for use.
[0034] Example 1
[0035] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0036] S2. Using an alternating spraying method, 1 wt% silane coupling agent solution (pH = 4), 0.2 wt% carbon oxide nanohorn solution (pH = 7), 1 wt% silane coupling agent solution (pH = 4) and 2 wt% ammonium polyphosphate solution (pH = 10) were deposited layer by layer on the cotton fabric surface; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C to dry for 10 minutes. The silane coupling agent solution, carbon oxide nanohorn solution, silane coupling agent solution, and ammonium polyphosphate solution are sprayed on the front and back sides of the fabric in the order of one cycle, and a total of one cycle is completed to obtain a flame-retardant cotton fabric.
[0037] Example 2
[0038] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0039] S2. 1 wt% silane coupling agent solution (pH = 4), 0.2 wt% carbon oxide nanohorn solution (pH = 7) and 2 wt% ammonium polyphosphate solution (pH = 10) were deposited layer by layer on the cotton fabric surface by alternating spraying method; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C to dry for 10 minutes. The silane coupling agent solution, carbon oxide nanohorn solution, silane coupling agent solution, and ammonium polyphosphate solution are sprayed on the front and back sides of the fabric in the order of one cycle, and a total of two cycles are performed to obtain a flame-retardant cotton fabric.
[0040] Example 3
[0041] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0042] S2. 1 wt% silane coupling agent solution (pH = 4), 0.2 wt% carbon oxide nanohorn solution (pH = 7) and 2 wt% ammonium polyphosphate solution (pH = 10) were deposited layer by layer on the cotton fabric surface by alternating spraying method; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C to dry for 10 minutes. The silane coupling agent solution, carbon oxide nanohorn solution, silane coupling agent solution, and ammonium polyphosphate solution are sprayed on the front and back sides of the fabric in the order of one cycle, and a total of three cycles are performed to obtain a flame-retardant cotton fabric.
[0043] Example 4
[0044] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0045] S2. 1 wt% silane coupling agent solution (pH = 4), 0.2 wt% carbon oxide nanohorn solution (pH = 7) and 2 wt% ammonium polyphosphate solution (pH = 10) were deposited layer by layer on the cotton fabric surface by alternating spraying method; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C to dry for 10 minutes. The silane coupling agent solution, carbon oxide nanohorn solution, silane coupling agent solution, and ammonium polyphosphate solution are sprayed on the front and back sides of the fabric in the order of one cycle, and a total of 4 cycles are performed to obtain a flame-retardant cotton fabric.
[0046] Comparative Example 1
[0047] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0048] S2. 1 wt% silane coupling agent solution (pH = 4) and 0.2 wt% carbon oxide nanohorn solution (pH = 7) were deposited layer by layer on the cotton fabric surface by alternating spraying method; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C and dried for 10 minutes. The silane coupling agent solution and the carbon oxide nanohorn solution are sprayed on the front and back sides of the fabric in the order of one cycle, and a total of 4 cycles are performed to obtain a flame-retardant cotton fabric.
[0049] Comparative Example 2
[0050] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0051] S2. 1 wt% silane coupling agent solution (pH = 4) and 2 wt% ammonium polyphosphate solution (pH = 10) were deposited layer by layer on the cotton fabric surface by alternating spraying method; 8 mL of the above solutions were measured each time, and each solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each side is sprayed, it is placed in an oven at 80°C to dry for 10 minutes. Spraying the silane coupling agent solution and the ammonium polyphosphate solution on the front and back sides of the fabric in this order is counted as one cycle, and a total of 4 cycles are performed to obtain a flame-retardant cotton fabric.
[0052] Comparative Example 3
[0053] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0054] S2. A 1wt% silane coupling agent solution (pH = 4) was deposited layer by layer onto the cotton fabric surface by spraying; 8 mL of ammonium polyphosphate solution was measured each time, and the solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each spraying, place in an oven at 80℃ to dry for 10 minutes. Each side is deposited 4 times to obtain a flame retardant cotton fabric.
[0055] Comparative Example 4
[0056] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven to dry for use;
[0057] S2. A 2 wt % ammonium polyphosphate solution (pH = 10) was deposited layer by layer onto the cotton fabric surface by spraying; 8 mL of ammonium polyphosphate solution was measured each time, and the solution was evenly sprayed on the fabric surface at a distance of 5 cm from the fabric surface using a desktop ultrasonic precision sprayer. The spraying area on one side of the fabric was 64 cm 2 After each spraying, place in an oven at 80℃ to dry for 10 minutes. Each side is deposited 4 times to obtain a flame retardant cotton fabric.
[0058] Comparative Example 5
[0059] S1. Wash the cotton fabric with a detergent in deionized water for 10 minutes, and then place it in an 80℃ forced air drying oven to dry for 10 minutes. After drying, immerse it in a 20g / L sodium hydroxide solution for 10 to 20 minutes for mercerization. After immersion, wash it with anhydrous ethanol and deionized water for multiple times until the pH value of the cotton fabric washing wastewater is neutral, and then place it in a 60℃ oven for drying for use, to obtain pure cotton fabric.
[0060] test
[0061] Figure 1Scanning electron microscope images of the washed and dried pure cotton fabric and the flame-retardant cotton fabric prepared in Example 4. It can be clearly observed that the surface of the pure cotton fabric is smooth and neat, and there are gaps between adjacent fibers. The surface of the cotton fabric treated with silane coupling agent, carbon oxide nanohorns, and ammonium polyphosphate becomes rough, and the adjacent fibers are completely connected and covered by the coating, and the gaps between the fibers disappear, indicating that the flame-retardant coating is successfully attached to the surface of the cotton fabric.
[0062] Figure 2 Thermogravimetric analysis of the washed and dried pure cotton fabric and the flame-retardant cotton fabric prepared in Example 4. See Table 1 for detailed data.
[0063] Table 1 Thermogravimetric characteristic parameters of pure cotton fabric and coated fabric
[0064]
[0065] It can be seen that in nitrogen atmosphere, the maximum thermal decomposition rate of pure cotton fabric (V max ) and the corresponding temperature (T max ) and 700°C, the residual carbon content was -2.03% / min, 382°C and 7.4wt% respectively. In comparison, the flame retardant cotton fabrics prepared in other embodiments and comparative examples except Comparative Example 1 had a T max 、V max This phenomenon is mainly attributed to the carbonization ability of carbon oxide nanohorns and the production of phosphoric acid and polyphosphoric acid during the thermal decomposition of ammonium polyphosphate, which promotes the catalytic dehydration and cross-linking of cellulose. At the same time, the combination of silane coupling agent, carbon oxide nanohorns and ammonium polyphosphate can effectively increase the residual carbon content at 700°C, that is, it can increase the residual carbon content of pure cotton fabric from 7.4wt% to 46.0wt%.
[0066] In air atmosphere, both pure cotton fabric and flame retardant cotton fabric show three thermal degradation stages. Figure 2 As shown in the figure, for pure cotton fabric, in the first stage (70-120℃), the physical adsorption water on the surface of cotton fabric is mainly removed; the second stage (200-400℃) can be attributed to the competition between dehydration carbonization and depolymerization of cellulose; the third stage (450-550℃) is the graded conversion of aliphatic carbon, part of which is converted into more stable aromatic carbon, while the other part is oxidized into water, carbon dioxide and carbon monoxide under the action of oxygen. The cotton fabric treated in the embodiment also shows three thermal degradation stages. As can be seen from Table 1, the W of the fabric treated in the embodiment is 700 and T max1It also showed a downward trend in air atmosphere, which was mainly attributed to the early thermal decomposition of APP, which catalyzed the dehydration and cross-linking of cotton fabric. The improvement of thermal stability of cotton fabric can be attributed to the formation of carbon layer in the second stage, in which the presence of silane coupling agent and oxidized carbon nanohorns improved the stability and density of the carbon layer, thereby hindering the diffusion of oxygen and inhibiting heat and mass transfer. Therefore, in the third thermal degradation stage, the T of coated cotton fabric max2 The thermal decomposition temperature is delayed. At the same time, the combination of silane coupling agent, carbon oxide nanohorns and ammonium polyphosphate can effectively increase the carbon residue at 700°C, that is, the carbon residue of pure cotton fabric can be increased from 0.7wt% to 34.5wt%.
[0067] The flame retardancy of the pure cotton fabric and the flame retardant cotton fabric prepared in the embodiment was evaluated by vertical flammability test and LOI test, wherein the vertical flammability test and LOI test were carried out according to the standards GB / T5454 and GB / T5455-2014, respectively. The test results are shown in Figure 3 and Table 2.
[0068] Table 2 LOI values and damage lengths of samples in various embodiments and comparative examples
[0069]
[0070] Once the pure cotton fabric was exposed to the fire, it was ignited, and the flame quickly spread to the top of the cotton fabric, and finally the cotton fabric was completely burned; during the combustion process, the afterburning time and smoldering time of the pure cotton fabric were 32s and 26s respectively. The flame-retardant cotton fabric prepared in Example 4 significantly enhanced the flame retardant properties of the fabric, and was able to self-extinguish immediately after the igniter was removed. During the entire combustion process, no smoldering phenomenon was observed. In addition, the residual charcoal morphology of the flame-retardant cotton fabric prepared in Example 4 remained intact after combustion, and the damaged length was small, decreasing from 30cm to 3.9cm, and its LOI value was 29.0±0.1%.
[0071] The above results show that, by using the spraying method of the present invention, the combination of silane coupling agent, carbon oxide nanohorns and ammonium polyphosphate can efficiently and quickly suppress the spread of flames with a small number of spraying times, and effectively reduce the damaged length of cotton fabrics.
[0072] In order to simulate the fire resistance of pure cotton fabric and flame retardant cotton fabric prepared in Example 1, the flame retardant cotton fabric was heated to 35 Kw / m 2 The sample was tested with cone calorimetry according to ISO 5660-1. The heat release rate curve is shown in Figure 4 , data see Table 3.
[0073] Table 3 Cone calorimetric characteristic parameters of samples in various embodiments and comparative examples
[0074]
[0075] It can be seen that the heat release rate value of pure cotton fabric is significantly higher than that of the flame-retardant cotton fabric prepared in each embodiment. Combined with Table 3, the samples of Example 4 and Comparative Examples 1, 2, 3, and 4 all reduce the heat release rate of pure cotton fabric, among which the combination of silane coupling agent, oxidized carbon nanohorns and ammonium polyphosphate is the preferred solution for inhibiting the spread of cotton fabric fire. The maximum average rate of heat release (MARHE) is usually used to determine the trend of fire development under realistic scale conditions. The smaller the value of MARHE, the better the flame retardant properties of cotton fabric. It can be seen from Table 3 that pure cotton fabric is extremely easy to burn, while the MARHE value of the flame-retardant cotton fabric prepared in the embodiment is significantly reduced, and the flame retardant properties of cotton fabric are improved. At the same time, the residual carbon content of the flame-retardant cotton fabric increased from 0.9% to 25.2%, from which it can be inferred that the combined coating of silane coupling agent, oxidized carbon nanohorns and ammonium polyphosphate promotes the formation of a dense protective carbon layer during combustion, thereby reducing the HRR, THR, MARHE, and Av-EHC values.
[0076] Figure 5 The scanning electron microscope images of the residual carbon after vertical combustion of the pure cotton fabric and the flame-retardant cotton fabric prepared in Example 4. It can be seen that the pure cotton fabric is completely burned, leaving only a small amount of fragile ash, and the cross-linked fiber structure is severely damaged. At high magnification, it can be observed that the strip-shaped fibers are full of holes and gaps, and oxygen and heat can easily pass through these holes and gaps, resulting in complete combustion of the pure cotton fabric. The flame-retardant cotton fabric prepared in Example 4 almost retains the original orthogonal plain weave structure of the cotton fabric after combustion. In addition, during the combustion process, the expansion of carbon and the generation of volatile gases cause many protruding and complete bubble-like structures to appear on the surface of the cotton fiber. This is mainly because the polyphosphoric acid produced by the thermal decomposition of ammonium polyphosphate can catalyze the cotton fabric and the oxidized carbon nanohorns to form a hybrid carbon layer containing N and P. The silicon dioxide produced by the hydrolysis of the silane coupling agent combines with it, so that the hybrid carbon layer can be used as an effective insulating layer to prevent the transfer of heat and oxygen, thereby playing an effect of preventing the spread of fire.
[0077] The structure of the hybrid carbon layer was evaluated using Raman spectroscopy, see Figure 6 , at 1330-1370cm -1 and 1570-1590cm -1 There are two broad peaks, marked as D peak and G peak. The D peak represents disordered carbon, and the G peak represents sp 2 Hybridized carbon atoms. The intensity ratio of D peak and G peak (I D / I G ) is usually used to evaluate the graphitization degree of the carbon layer. D / I G The lower the value of, the higher the degree of graphitization of the carbon layer. D / IG The value dropped from 1.33 of pure cotton fabric to 0.89. This result shows that the prepared coating formed a highly graphitized carbon layer during the combustion process, which is beneficial to improve the flame retardant properties of cotton fabric.
[0078] When the flame-retardant cotton fabric prepared by the present invention is exposed to fire, ammonium polyphosphate can simultaneously serve as an acid source and a gas source to produce highly cross-linked polyphosphoric acid, ammonia and water at about 300°C. Polyphosphoric acid promotes the dehydration and carbonization of cotton fabric and oxidized carbon nanohorns. In addition, oxidized carbon nanohorns can enhance carbonization and improve the stability of the carbon layer. The hydrolysis product of the silane coupling agent forms inorganic silicon dioxide during the thermal degradation process, which can serve as an insulating layer to protect the cotton fabric from the fire and can also improve the thermal stability of the carbon layer. The phosphorus-nitrogen-silicon hybrid carbon layer formed by the oxidized carbon nanohorns and the silane coupling agent in combination with phosphorus can effectively inhibit the release of volatile combustibles. At the same time, the expansion of the carbon layer and the generation of volatile gases lead to the appearance of a large number of protruding, complete bubble-like structures on the surface of the cotton fabric, which hinder the transfer of heat and oxygen and make the cotton fabric self-extinguishing.
[0079] According to existing reports, patent CN 109944070A discloses a self-extinguishing flame-retardant cotton fabric and its preparation method and application. 5 to 20 flame-retardant unit layers (four layers of silane coupling agent / sodium alginate / silane coupling agent / ammonium polyphosphate or four layers of silane coupling agent / ammonium polyphosphate / silane coupling agent / sodium alginate) are deposited on the surface of the cotton fabric. The coated cotton fabric in the embodiment does not disclose the afterburning time and smoldering time in the vertical combustion test. The best group has a carbon residue rate of 47.4% and 27.3% in nitrogen and air atmospheres at 700°C, respectively, and a carbon residue length of 4.5 cm. The area ratio of the D peak to the G peak of the carbon residue of the burned coated cotton fabric is 3.22, and the carbon residue length of the coated cotton fabric tested for flame retardancy after 30 washes according to the standard is 8.1 cm, which has a self-extinguishing effect. The flame retardant cotton fabric prepared by this method has a residual carbon rate of 46.0% and 34.5% in nitrogen and air atmospheres at 700°C, respectively. The damaged length of the coated cotton fabric after burning is 3.9 cm. The area ratio of the D peak to the G peak of the carbon residue of the coated cotton fabric after burning is 0.89, and the flame retardant effect is significantly better than the former.
[0080] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a flame-retardant cotton fabric assembled layer by layer with spraying assistance, characterized in that: The following steps are involved: S1. After the cotton fabric is washed and dried, it is soaked in a sodium hydroxide solution of a set concentration. After the soaking is completed, it is washed again until the pH value of the cotton fabric washing wastewater is neutral, and the cotton fabric is dried; S2. spraying 1 to 5 wt% silane coupling agent solution, 0.1 to 1 wt% oxidized single-walled carbon nanohorn solution, 1 to 5 wt% silane coupling agent solution and 2 to 5 wt% ammonium polyphosphate solution on the surface of the cotton fabric in sequence, drying the cotton fabric after each spraying, and spraying in a cycle until the desired number of layers is reached; S3. Drying the cotton fabric to obtain the desired flame-retardant cotton fabric.
2. The method for preparing a spray-assisted layer-by-layer flame-retardant cotton fabric according to claim 1, characterized in that: The number of cycles of the cyclic spraying is 1 to 4 times.
3. The method for preparing a flame-retardant cotton fabric assembled layer by layer with spraying assistance according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane.
4. The method for preparing a spray-assisted layer-by-layer flame-retardant cotton fabric according to claim 1, characterized in that: The single spraying amount of the silane coupling agent solution, the oxidized single-walled carbon nanohorn solution and the ammonium polyphosphate solution is the same, and the spraying ratio is 1mL:8cm 2 .
5. The method for preparing a spray-assisted layer-by-layer flame-retardant cotton fabric according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.25 to 0.5 mol / L, and the soaking time is 10 to 20 minutes.
6. The method for preparing a spray-assisted layer-by-layer flame-retardant cotton fabric according to claim 1, characterized in that: In the steps S1 to S3, the drying temperature is 50 to 80°C.
7. A flame retardant cotton fabric, characterized in that: 1-4 flame retardant structural layers are deposited on the surface of the flame retardant cotton fabric, and the flame retardant structural layers are composed of a silane coupling agent layer, an oxidized single-walled carbon nano-horn layer, a silane coupling agent layer, and an ammonium polyphosphate structural layer, which are compounded in sequence from the outside to the inside. The thickness of each flame retardant structural layer is 160 μm, and the thickness of the silane coupling agent layer, the oxidized single-walled carbon nano-horn layer, the silane coupling agent layer, and the ammonium polyphosphate structural layer are all 40 μm.
Citation Information
Patent Citations
Self-extinguishing flame-retardant cotton fabric and preparation method and application thereof
CN109944070A